FAKTOR – FAKTOR YANG MEMPENGARUHI IMPOR GULA INDONESIA - Muthiah Putri; Sri Ulfa Sentosa (Universitas Negeri Padang, 2021)
This study aims to analyze the Effect of Exchange Rate, Production, GDP and Inflation on Sugar Imports in Indonesia, either partially or simultaneously.This type of research is classified as quantitative research. This research was conducted in Indonesia using data obtained from the Central Statistics Agency (BPS), coumtraden.un.org (United Nations International Trade Statistics Database), the World Bank, and the International Monetary Fund (IMF). The data used are annual data from 1989 to 2020. The data analysis technique uses multiple linear regression with t test and F test. The results showed that (1) the exchange rate had a positive and significant effect on sugar imports in Indonesia with a regression coefficient of 0.554 and the value of tcount >ttable (2.1697 > 2.052) or significant < significance (0.012 < 0.05). (2) production has a negative and insignificant effect on sugar imports in Indonesia with a regression coefficient of -0.759 and a production tcount > ttable (-1.602 < 2.052) or significant > significance (0.121 > 0.05). (3) GDP has a positive and significant effect on sugar imports in Indonesia with a regression coefficient of 1.293 and tcount GDP > ttable (3.395 > 2.052) or significant <significance (0.002 < 0.05). (4) Inflation has a negative and insignificant effect on sugar imports in Indonesia with a regression coefficient of -0.003 and an inflation tcount > ttable (0.722 < 2.052) or significant > significance (0.476> 0.05). (5) exchange rate, production, GDP and inflation have positive and significant effect together on sugar imports in Indonesia, the results of the analysis show that the Fcount 40.999 > Ftable 2.73 (0.000 < 0.05).